2023
DOI: 10.3390/ijms24032506
|View full text |Cite
|
Sign up to set email alerts
|

VT68.2: An Antibody to Chondroitin Sulfate Proteoglycan 4 (CSPG4) Displays Reactivity against a Tumor-Associated Carbohydrate Antigen

Abstract: The anti-CSPG4 monoclonal antibodies (mAbs) have shown anti-tumor activity and therapeutic potential for treating breast cancer. In addition, CSPG4 is a dominant tumor-associated antigen that is also involved in normal-tissue development in humans. Therefore, the potential for off-tumor activity remains a serious concern when targeting CSPG4 therapeutically. Previous work suggested that glycans contribute to the binding of specific anti-CSPG4 antibodies to tumor cells, but the specificity and importance of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous studies demonstrated the specificity of CSPG4 expression in triple-negative breast cancer and the role of sulfated chondroitin in the aggressive behavior of breast cancer cells in vitro [14,15]. Rather than using a vaccination approach, the study by Nounamo et al [16] describes the therapeutic potential of an anti-CSPG4 monoclonal antibody (Mab VT68.2). Their study demonstrates that tumorassociated glycans mediate the binding of Mab VT68.2 to breast cancer cells and that this binding reduces both the viability and metastatic potential of these cells in vitro.…”
Section: Immune Targeting Of Tumor Cellsmentioning
confidence: 99%
“…Previous studies demonstrated the specificity of CSPG4 expression in triple-negative breast cancer and the role of sulfated chondroitin in the aggressive behavior of breast cancer cells in vitro [14,15]. Rather than using a vaccination approach, the study by Nounamo et al [16] describes the therapeutic potential of an anti-CSPG4 monoclonal antibody (Mab VT68.2). Their study demonstrates that tumorassociated glycans mediate the binding of Mab VT68.2 to breast cancer cells and that this binding reduces both the viability and metastatic potential of these cells in vitro.…”
Section: Immune Targeting Of Tumor Cellsmentioning
confidence: 99%